Multimodality Discourse Analysis of Cover Novel ‘Laut Bercerita’ - Fitriah, Fitriah; Suyudi, Ichwan (ITScience (Information Technology and Science), 2025)
The analysis of the cover novel Laut Bercerita by Leila S. Chudori, as described in the novel, reveals specific design elements and choices that contribute to the visual disclosure of the novel. The study focuses on the cover of the novel as a form of visual disclosure and the identity of the novel. It aims to understand how the cover of a novel represents the contents of the story to attract the attention of readers using the analyzing with the multimodality discourse analysis. Multimodal discourse analysis is required to delve deeper into the meaning or message to be conveyed through the cover of novel Laut Bercerita. Acknowledging that the cover novel is the identity of the novel, the study places importance on visual as a means of conveying a message to the public through images. The research method employs a descriptive qualitative approach, emphasizing an in-depth analysis using visual communication as the primary lens by using strategy multimodal discourse analysis. For this case, that's why multimodal discourse analysis is the best approach to use in this research because, in MDA, the deep understanding of the combination of verbal elements, visual elements, and image in the cover will be analyzed, and supported by systemic functional linguistic in focusing linguistic aspect from the object. Data collection involves observation of the novel cover and a literature study. The combination of direct observation and background research provides a comprehensive understanding of both visual elements and contextual information